Studies of electron cyclotron resonance ion source beam formation, transport and quality - Toivanen, Ville (2013)
This thesis presents the results of a broad study investigating diﬀerent possibilities to improve the performance of the JYFL 14 GHz Electron Cyclotron Resonance Ion Source (ECRIS). The experimental work includes studies of ECRIS plasma, ion beam formation and beam transport, all of which contribute to the properties of ion beams produced with ECR ion sources. In particular, it is shown that the degradation of beam quality due to the formation of hollow beam structure is inﬂuenced by phenomena originating from all of these categories. The eﬀects of ﬁne tuning the frequency of the plasma heating microwaves of the JYFL 14 GHz ECRIS are presented, showing that the frequency tuning can inﬂuence the ion beam properties. It is demonstrated that the ion beams produced with the ion source are not completely space charge compensated during the ﬁrst section of the beam transport, and the space charge eﬀects in this region have signiﬁcant impact on the beam properties. Also, it is shown that mitigating these eﬀects can lead to substantial improvement in beam quality. The temporal stability of ion beams produced with ECR ion sources is discussed and it is shown that the beams exhibit fast beam current oscillations in the 102 − 103 Hz region, characteristics of which depend on the ion source tuning. Experiments with the so-called collar structure are presented, providing new insight into the plasma conditions near the ion extraction. As a culmination of the thesis work, a new extraction system has been designed and constructed for the JYFL 14 GHz ECRIS. It is shown that the new system provides improved performance compared to the old one in terms of extracted beam currents, beam quality and transmission eﬃciency.